Current Trends for Blockchain and Smart Contracts (In Financial Services) - Pablo Garcia Bringas; Iker Pastor-López; Giuseppe Psaila (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
The most popular virtual currency (bitcoin) has become so popular because it relies on the concept of Distributed Ledger, realized by means of a technology known as BlockChain. This technology removes the need for third parties (such as authorities) that authorize transactions; in fact, it is a peer-to-peer network where consensus to transactions is given by peers. Furthermore, the distributed nature of BlockChain ensures a high-level of robustness to attacks. However, since its birth (a decade ago) many evolutions have been introduced: now, we distinguish between permissionless and permissioned BlockChains, the concept of smart contract is now supported, and various platforms are available. The contribution of this paper is to provide novices with the current trends, in particular by discussing the adoption of BlockChain technology in financial services.
Keywords: L86; 330; BlockChain characterization; Smart contracts; Perspective BlockChain in financial services